Kompleksitas Suara Ester: Negosiasi Subaltern atau Privilese? - Setiawan, Yohanes (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2024)
Marginalized groups are often denied an authentic voice within dominant power structures. This issue is relevant to understanding representation, power, and inequality in different social, political, and cultural contexts. This article seeks to explore the complexities of Esther's representation and identity from the perspectives of the subaltern and liberation theology. It critically examines Gayatri Chakravorty Spivak's question, "Can the subaltern speak?" by analyzing Esther's dual identity as subaltern and non-subaltern.  Using textual analysis, this study aims to deepen understanding of how Esther's narrative challenges traditional notions of power, agency, and representation. The analysis found that Esther's voice can only be heard when she is socially aligned with the dominant authority structure in the socio-political context.